Exploring the Relationship Between Pre-School-aged Animated Television and Agriculture: A Content Analysis of Disney Junior's Mickey Mouse Clubhouse - Cassaundra Dietrich; Emily Buck; Annie Specht (Journal of Applied Communications, 2015)
Understanding how modern preschool television series are framing agriculture can help agricultural communicators and educators gain insight into what schemata preschoolers have developed about agriculture prior to participation in formal education and non-formal youth programming (such as 4-H). Framing theory and schema theory play a role in a developing child’s absorption and interpretation of television programming content. Considering the potential implications of television consumption by preschoolers, this study aims to use summative content analysis methods to examine how agriculture is framed in current preschool-aged animated television programming. This analysis reviewed two iTunes collections of Mickey Mouse Clubhouse, each of which contained five episodes of the show. The two iTunes collections selected — “Mickey and Donald Have a Farm” and “Mickey’s Farm Fun-Fair!” — were chosen because of their farm-centric themes. While content analysis revealed Mickey Mouse Clubhouse does frame agriculture in a positive context, it also uncovered a lack of depth in regard to educational lessons related to production agriculture. Additionally, several inaccuracies and improbable scenarios regarding production livestock, farm machinery and crops were discovered.
Keywords: Preschool; television; agriculture; Disney; Mickey Mouse Clubhouse; farm; framing theory; schema; animation; cartoons; Association for Communication Excellence Conference